Substrato e solução nutritiva desenvolvidos a partir de efluente de biodigestor para cultivo do meloeiro - Villela Jr., Luiz V. E. [UNESP]; De Araújo, Jairo A. C. [UNESP]; Barbosa, José C. [UNESP]; Perez, Luiz R.B. (FapUNIFESP (SciELO), 2007)
Looking for the sustainability of a small farming enterprise, the present study focused the benefit of the biodigestor effluent resulting from the anaerobic fermentation of the bovine manure in a soilless melon plant experiment. The research was conducted in Jaboticabal, in the State of Sao Paulo, Brazil, at latitude of 21° 15' 22'' S and a longitude of 48° 18' 58'' W. The melon plant (Cucumis melo L. cv Bonus n° 2) was grown with substrate, seedling obtained in 10/2003. An experimental design was adapted in a randomized block with 16 treatments and 5 replications in a factorial 4 x 4 (4 substrates and 4 nutrient solutions). The 4 substrates were made up of different proportions in volume of the blend composition taking into consideration both the solid part of the biodigestor effluent and the washed raw sand. The 4 nutrient solutions were made up of the liquid part of the biodigestor effluent (biofertilizer) in substitution to the mineral water soluble fertilizers. The addition of the effluent in the sand led to a more rapid vegetative growth, a more precoceous crop with heavier fruits and a much better yield of melon crop. The mineral water soluble fertilizers used in the cultivation of plants in substrates can be partially replaced by the biofertilizer studied.
Substrate and nutrient solution developed using a biodigestor effluent for melon cultivation
Keywords: Biofertilizer; Cucumis melo L; Hydroponics; Reutilization of residue; Bovinae; Cucumis; Cucumis melo